Setting the scene: a scoping review of gambling research in Ghana - Badu, Emmanuel; Hallett, Jonathan; Vujcich, Daniel; Crawford, Gemma; Bellringer, M.E. (2023)
Ghana, like many other African countries, has seen a rapid expansion in gambling industry activity in the last decade with sports betting becoming a popular pastime among young Ghanaian males. The proliferation of land based, and online gambling operations presents a significant public health threat to the citizenry. Yet little is known about gambling participation and harms, the size of the gambling market and the role of the gambling industry in influencing and perpetuating gambling behaviour in Ghana. The aim of this study was to contribute to understanding the extent of gambling research in Ghana by mapping out what the current literature indicates. Six databases were searched for peer-reviewed journal articles that focused on gambling in Ghana. The findings from this review demonstrate gambling research in Ghana is in a nascent state with a predominant focus on individual factors and limited consideration of public health. The implications for future research are highlighted, including the requirement for a nationally representative study to understand the prevalence of gambling participation and harm, and the role of the gambling industry. Public health action grounded in sound evidence is urgently required to address the individual and community level problems associated with this harmful commodity.